Investigating the relationship between knowledge management and social capital - Azimi, Hossein (goodwood publishing, 2021)
Purpose: The purpose of this study is to establish the relationship between knowledge management and social capital in education from the perspective of human resource managers of Tehran industrial companies. Research methodology: A knowledge management questionnaire and social capital questionnaire were used to collect data. The reliability of the questionnaires was 0.909 and 0.912 by Cronbach's alpha method, respectively. Kolmogorov-Smirnov tests, regression, and Pearson coefficient were used to analyse the data. Results: The results show that there is a significant relationship between social trust and knowledge management, also there is a significant relationship between networks and knowledge management; In addition to the above, it was shown that there is a significant relationship between cooperation and knowledge management and between relationships and knowledge management. Limitations: The practical and usable environment for the results of this study is the educational environment. Contribution: Our research can be very useful for researchers in this field due to the accuracy we had in doing the work and using its results in the educational environment and industrial companies.